Sexual Harassment in the Workplace: Consequences and Perceived Self-Efficacy in Women and Men Witnesses and Non-Witnesses - Daniela Acquadro Maran; Antonella Varetto; Cristina Civilotti (Behavioral Sciences, 2022)
Despite the numerous advances made in Italy over the years in the study of sexual harassment in the workplace (SHW), research has focused exclusively on victims, perpetrators, and their relationships, and not on the consequences that the experience of sexual harassment can produce in witnesses. The present study aims to address this gap by examining how the indirect experience of SHW, in conjunction with variables such as gender, age, self-efficacy, and coping strategies, affects the mental health status of witnesses of SHW. A sample of 724 employees completed a questionnaire that included a modified version of the Sexual Experience Questionnaire (SEQ), the Oldenburg Burnout Inventory (OLBI), the General Health Questionnaire (GHQ), the Satisfaction With Life Scale (SWLS), and the Emotional Self-Efficacy Scale (RESE). Of the group, 321 participants reported witnessing sexual harassment in the workplace (28.2% of women and 16.2% of men). Results show that witnesses were younger than participants who described themselves as non-witnesses. Results also show that women and men who were witnesses were more likely to suffer the emotional and psychological consequences of the experience than non-witnesses. In addition, female witnesses expressed more positive emotions than men, which enabled them to manage their anxiety and emotional states when triggered in response to sexual harassment in the workplace. Finally, a significant association was found between perceptions of mental health and age, gender, experience with SHW, and self-efficacy strategies. The findings underscore the importance of sexual harassment intervention in the workplace, women and men who witness sexual harassment suffer vicarious experiences, psychological impact, exhaustion, disengagement, and negative feelings.